Corporate social responsibility of private game reserves in the Eastern Cape Province - Motala, Amina Sadiq (Rhodes University, Faculty of Commerce, Department of Management, 2013)
The primary aim of this research study was to determine the current state of practice of corporate social responsibility (CSR) within the ecotourism based private game reserve (PGR) industry in the Eastern Cape Province of South Africa. According to Carroll (1991) four kind of responsibilities constitute total CSR, namely economic, legal, ethical and philanthropic responsibilities. Given the context of this research a fifth responsibility concerning environmental responsibilities was added to Carroll 's (1991) pyramid ofCSR. A descriptive and illustrative case study approach, within the phenomenological research paradigm, was used for the purpose of this research. The unit of analysis is the Indalo group, the Association of Eastern Cape Private Game Reserves, made up of 12 ecotourism based PORs. As the current research focused on eight of the twelve PGRs a mUltiple case study was employed. To give effect to the aim a number of research objectives were identified. Firstly to desclibe and assess the current practice in implementing CSR within the ecotourism based PGR industry in the Eastern Cape Province. Secondly, to assess and evaluate the involvement of ecotourism based PGRs in the Eastern Cape Province in each of the five responsibilities comprising CSR. Thirdly, to identify the challenges faced by ecotourism based PGRs in the Eastern Cape Province with regard to the implementation of CSR initiatives. Lastly to provide pertinent conclusions and recommendations with regard to CSR strategies within the ecotourism based PGR industry in the Eastern Cape Province. Data were collected by means of in-depth interviews with the managers of each reserve. In addition the researcher conducted focus interviews with administrative employees at each of the member reserves of the Indalo group. Additionally the managers of each reserve were requested to respond to a structured five point Likert scale questionnaire based on the research by Aupperle, Carroll and Hatfield (1985). This research study found that the current practice at the Indalo group is towards a strategic, long term approach to CSR that aids in the development of a 'sustainable organisation.' The aspect of ' empowerment' emerged as the essence of the current practice ofCSR of the Indalo group. Based on the current practice it was concluded that the Indalo group is actively involved in the specific components of CSR namely, environmental, economic, legal, ethical and philanthropic responsibilities. With regard to the environmental responsibilities it was concluded that the environment is the foundation upon which all other components of CSR rest. In addition it was concluded that the economic responsibilities, if managed well, are key to unlocking the CSR potential of a reserve as well as ensuring widespread economic development. In terms of the legal and ethical responsibilities it was concluded that tourism policies both at the national and international level have not aided in the development of a CSR agenda of the Indalo group. Furthermore managers of the reserves have been instrumental in cultivating their own legal culture of CSR based on their experience in the tourism industry and their ethical stances. In terms of the philanthropic responsibilities it can be concluded that charitable activities that are long term and strategic in nature allow for direct and indirect benefits to all parties involved. Overall, it can further be concluded that despite Hudson and Miller's (2005:5) view that the "tourism industry is well hehind other industries in terms of CSR" the Indalo group is moving forward in terms of rooting CSR into their everyday operations.
Keywords: Social responsibility of busines -- South Africa -- Eastern Cape; Game reserves -- South Africa -- Eastern Cape; Ecotourism -- South Africa -- Eastern Cape; Environmental responsibility -- South Africa -- Eastern Cape